Antibodies against peripheral nerve antigens in chronic inflammatory demyelinating polyradiculoneuropathy. Issue 1 (December 2017) - Querol, Luis; Siles, Ana; Alba-Rovira, Roser; Jáuregui, Agustín; Devaux, Jérôme; Faivre-Sarrailh, Catherine; Araque, Josefa; Rojas-Garcia, Ricard; Diaz-Manera, Jordi; Cortés-Vicente, Elena; Nogales-Gadea, Gisela; Navas-Madroñal, Miquel; et al.
Abstract Chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) is a heterogeneous disease in which diverse autoantibodies have been described but systematic screening has never been performed. Detection of CIDP-specific antibodies may be clinically useful. We developed a screening protocol to uncover novel reactivities in CIDP. Sixty-five CIDP patients and 28 controls were included in our study. Three patients (4.6%) had antibodies against neurofascin 155, four (6.2%) against contactin-1 and one (1.5%) against the contactin-1/contactin-associated protein-1 complex. Eleven (18.6%) patients showed anti-ganglioside antibodies, and one (1.6%) antibodies against peripheral myelin protein 2. No antibodies against myelin protein zero, contactin-2/contactin-associated protein-2 complex, neuronal cell adhesion molecule, gliomedin or the voltage-gated sodium channel were detected. In IgG experiments, three patients (5.3%) showed a weak reactivity against motor neurons; 14 (24.6%) reacted against DRG neurons, four of them strongly (7.0%), and seven (12.3%) reacted against Schwann cells, three of them strongly (5.3%). In IgM experiments, six patients (10.7%) reacted against DRG neurons, while three (5.4%) reacted against Schwann cells. However, results were not statistically significant when compared to controls. Immunoprecipitation experiments identified CD9 and L1CAM as potential antigens, but reactivity could not be confirmed with cell-based assays. In summary, we describe a diverse autoantibody repertoire in CIDP patients, reinforcing the hypothesis of CIDP's pathophysiological heterogeneity.